Does highway accessibility influence local tax factors? Evidence from German municipalities - Luisa Dörr; Stefanie Gaebler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We examine how highway accessibility influences tax policy. We exploit the stagewise expansion of the "Baltic Sea highway" in the East German state Mecklenburg-Western Pomerania as the largest contiguous highway construction project in Germany since 1945. For non-agglomeration municipalities that lie on a convenient route between two larger cities the access and opening year are close to random. Results from difference-in-differences estimations and an event study approach show that highway access influences local tax setting in municipalities within 5 to 10 km road distance. Improved accessibility increases property tax factors persistently by roughly 6 percentage points. Our effects are driven by peripheral municipalities, while we do not find an influence on core municipalities. Additionally, improved accessibility gives rise to a shift of population and economic activity from the periphery to the core.
Keywords: H54; H71; O18; 330; highway; infrastructure; accessibility; tax factors; municipalities; localgovernments